TRAFICUL DE PERSOANE – O PROBLEMĂ SOCIALĂ (ANALIZA CHESTIONARULUI) - MORARI, bibliotecar principal, Filiala „Târgu-Mureș”, Elena (BIBLIOPOLIS, 2020)
In line with the National Plan for Preventing and Combating Trafficking in Human Beings for the years 2014-2016, we intend to analyze this social issue. Thus, along with a series of activities of informing and educating the users, during the year we also conducted a sociological research on the Socio-Economic Profile of potential victims of trafficking in women. Through this, we aim to highlight the perception and attitude of the users of the library on the phenomenon of trafficking in human beings.